Study of the metabolic stability profiles of perampanel, rufinamide and stiripentol and prediction of drug interactions using HepaRG cells as an in vitro human model - Meirinho, Sara (2023)
New-generation antiepileptic drugs as perampanel, rufinamide and stiripentol emerged as alternatives in chronic epilepsy polytherapy. Hence, their metabolic stability and potential involvement in relevant drug-drug interactions (DDI) are of great clinical interest, being HepaRG cells herein used as an in vitro human model. To characterize their metabolic stability profiles, HepaRG cells were incubated with perampanel (1 μM), rufinamide (100 μM) or stiripentol (5 μM) for 12-h. HepaRG cells, pretreated with known CYP450 isoenzymes inducers (rifampicin, phenytoin, phenobarbital, omeprazole and carbamazepine), were also incubated with perampanel, rufinamide or stiripentol to assess possible DDI mediated by CYP450 induction. Results suggest a considerable decrease in perampanel and stiripentol concentrations over 12-h; contrary, rufinamide concentrations did not variated. Cells pretreatment with all inducers significantly decreased stiripentol concentrations (between 20.3% and 31.9%), suggesting a considerable potential for DDI. Rufinamide concentrations only decreased when preincubated with rifampicin and with the highest tested concentrations of the remaining inducers. Perampanel levels decreased with rifampicin, carbamazepine and phenobarbital, supporting the involvement of CYP3A4-mediated metabolism. Besides relevant information concerning the metabolic stability profile and potential DDIs of the new antiepileptics here studied, it was also reinforced the HepaRG cells suitability as a reliable in vitro model to foresee in vivo metabolism in humans.